Pemberian Rebusan Jahe dan Madu Sebagai Terapi Komplementer Pada An.R Dengan Masalah Ispa di Desa Kutabawa - Siti Aisah; Eko Sari Ajiningstyas; Sudiarto S (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Background: Based on data from the Kutabawa Village Midwife in 2022, the ISPA rate in toddlers reaches 7%, which is the highest case compared to others. Acute respiratory infection (ARI) is an acute infectious disease that attacks one or more parts of the respiratory tract, from the nose to the alveoli. Treatment of ARI can use pharmacology and non-pharmacology. Non-pharmacology can use ginger and honey decoction, which is effective for reducing ARI symptoms such as coughs and runny noses.The purpose: To determine the effectiveness of giving ginger and honey decoction as a complementary therapy to an R with ARI problems. Methods: This study used a case study method with respondents suffering from mild ARI (cough, runny nose, discharge, and having not received pharmacological treatment) and focusing on giving ginger and honey decoction as complementary therapy to children with ARI. Using three instruments, namely observation sheets, interview sheets, and the Gordon assessment format, This research was carried out in Kutabawa Village for 5 days, from March 15–20, 2023. Results: After 5 days of action, the frequency of the child's cough decreased. Conclusion: Giving ginger and honey decoction to An.R. for 5 days, which is given twice a day, is effective as a complementary therapy in cases of mild ARI.